Legal Processes Of Child Sexual Violence Victims - Handoko, Panggung (International Journal of Educational Research & Social Sciences, 2022)
Study aims to find out how the legal protection efforts for victims of sexual violence-rape children and how the impact received by the child, and how the system of imposing sanctions received by perpetrators of the crime of rape whose age is also still under the age decided by the District Court. Surabaya. This study uses a normative juridical approach. In this research, the main source is legal material, not data or social facts. The legal materials consist of primary legal materials and secondary legal materials. The data analysis used is descriptive analysis, which begins with grouping the same data and information according to sub-aspects and then interprets to give meaning to each sub-aspect and its relationship to one another. From the results of the study, it can be concluded that legal protection for child victims of rape has not met expectations and is very worrying. Because they have to suffer prolonged trauma, due to the actions of the perpetrators. Meanwhile, the imposition of sanctions for perpetrators who are also minors, is considered still far from paying attention to the rights and negative negative consequences of the victim because the decision is considered not to be in accordance with the provisions and expectations.